Preparation method of cuprous oxide polycrystalline particles with micro-nano structure
By using small molecule amines to regulate the crystal size during the preparation of copper oxide particles, the problem of copper oxide particles being difficult to have low agglomeration and large specific surface area is solved, and the micro-nano structure construction of copper oxide polycrystalline particles and multi-stage controllable regulation of crystal size are achieved, improving the performance of the material.
Patent Information
- Application Number
- CN202510292930.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-13
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-03-13
AI Technical Summary
The prior art is difficult to have both the low agglomeration and large specific surface area of copper oxide particles, resulting in poor material performance expression and difficult to achieve small-sized crystal size regulation of multi-crystal particles.
By dropping the aqueous organic amine solution into the aqueous solution of divalent copper salt and adding a reducing agent solution after stirring the reaction, the reaction conditions and the type of small molecule amine are controlled to accurately regulate the small-sized crystal size that constitutes the copper oxide polycrystalline particles.
The micro-nano structure of cuprous oxide polycrystalline particles is realized, and the particles have a large specific surface area and good dispersion. At the same time, by regulating the types of small molecule amines, the crystal size can be adjusted within the range of 40~600 nm and the performance of the material can be improved.
Smart Images

Figure CN119822397A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cuprous oxide polycrystalline particle preparation, and relates to a method for preparing a micro-nano structure. Background Art
[0002] Cuprous oxide powder is a common inorganic material and is widely used in the fields of antibacterial, coating, and ship antifouling. Currently, liquid phase reduction is one of the most common chemical methods for batch preparation of cuprous oxide powder. The related methods of synthesizing cuprous oxide particles by liquid phase reduction at normal pressure under near room temperature have been widely studied, and a large number of literatures have been produced, such as literature 1 (J. Am. Chem. Soc., 2024, 146(14): 9665-9678. ), literature 2 (ACSSustainable Chem. Eng., 2023, 11(44): 15931-15940. ), literature 3 (Appl Organomet Chem., 2024, 38(8)) and literature 4 (ACS Sens., 2019, 4(11): 3051-3055.). However, the cuprous oxide particles synthesized in these documents are generally simple shapes such as cubic, polyhedral or spherical. The particles do not have a complex structural composition and cannot simultaneously meet the requirements of low particle agglomeration and large specific surface area, which is not conducive to the performance expression of the material.
[0003] Reference 5 (Small, 2023, 19(26), 2300394.) and reference 6 (Chem. Rev., 2016, 116(18): 10983-11060.) both mentioned that constructing micro-nano structures can make materials have both the high specific surface area and high catalytic activity of nanomaterials and the characteristics of large-sized materials that are not easy to agglomerate. By constructing nano-sized units on the surface of micron-sized particles or performing precise morphological modifications, nano-units with special effects can be connected to the macroscopic particles themselves, so that the material has certain characteristics of nano-scale materials while having a larger scale, such as structural color phenomenon and surface plasmon resonance (SPR) of nanoparticles. For applications in some fields, the construction of micro-nano structures also has other functions. For example, reference 7 (Adv. Funct. Mater., 2021, 31(12), 2008352.) mentioned that cuprous oxide can be precisely fitted to the surface of microorganisms through the constructed micro-nano structures, thereby maximizing the contact and killing of viruses. In addition, many performance expressions of powder materials are closely related to the specific surface area of the powder materials. The larger the specific surface area, the better the performance of the material. By constructing micro-nano structures, the particles can obtain a larger specific surface area through the nanoscale units on the surface of the particles, and because of the larger particle size (micrometer or near micrometer), it is less likely to agglomerate than nanoparticles, and has better dispersibility when used. In summary, the construction of micro-nanostructured cuprous oxide spherical particles with nanometer-sized units is of practical significance.
[0004] Among the current patents for synthesizing micro-nanostructured cuprous oxide particles, the polyhedral cuprous oxide particles synthesized in patent CN104261457A have smooth surfaces, and the morphologies include hexahedron, octahedron, polyhedron, and sphere, and do not have the assembly or modification structure of small-sized units. Patent CN111285394B uses polyol to dissolve the copper source, which has high synthesis cost and is not conducive to the post-treatment of waste liquid. Patent CN113083239B has a complex reaction system, and the raw materials include wood pulp, TEMPO, sodium carbonate, sodium citrate, copper sulfate pentahydrate, sodium hypochlorite and sodium bromide. Too many reaction raw materials are not conducive to cost reduction and simplification of the synthesis process. Patent CN104772142A and document 8 (CrystEngComm, 2012, 14: 278-285.) both obtain micro-nanostructured cuprous oxide spheres, but they need to be subjected to high-temperature and high-pressure hydrothermal or solvent thermal reactions, which are harsh conditions and have certain risks.
[0005] Currently, the size control of cuprous oxide particles is mainly aimed at the macroscopic size of the particles. For example, reference 9 (Part. Part. Syst. Charact., 2020, 37, 2000106.) obtained cuprous oxide spheres of different particle sizes by controlling the concentration of copper salts and using acid etching, while reference 10 (Electroanalysis, 2017, 29: 2773-2779.) found that the introduction of Au would significantly change the particle size of cuprous oxide macroscopic particles. However, there is no relevant literature on the multi-level controllable regulation of the size of small-sized crystals constituting cuprous oxide polycrystalline particles or small-sized particles constituting cuprous oxide assembled particles. It is speculated that this is because the current synthesis of micro-nanostructured cuprous oxide generally requires the use of macromolecular dispersants, such as patents CN108680625A, CN106493381B, CN104445358B, document 11 (Adv. Mater., 2024, 36, 2313212.) and document 12 (Acta Chimica Sinica, 2009, 67(14): 1591-1596.), which use macromolecular or long carbon chain dispersants such as polyethylene glycol, polyvinyl pyrrolidone, sodium oleate, hexadecyltrimethylammonium bromide, and sodium dodecyl sulfate. On the one hand, these dispersants are easy to remain in the product, affecting the purity and increasing the synthesis cost. On the other hand, they actually play the role of templates to limit the growth size of individual cuprous oxide crystal particles, so that cuprous oxide particles exist in the form of small-sized particles and further agglomerate to form micro-nano structures. Therefore, changing the concentration of copper salts and other means cannot significantly change the size of small crystals, but will only increase the number of small crystals and lead to an increase in the size of macroscopic particles. However, due to the large differences in chemical composition and structure between various macromolecular dispersants, their functional group types, branched chain structures, aqueous solution viscosities, acidity and alkalinity are all different. In the synthesis system, it is impossible to simply replace macromolecular dispersants to achieve the purpose of controlling the size of small-sized particles.
[0006] Among other patents or papers on the synthesis of cuprous oxide polycrystals, CN101905899A synthesized cuprous oxide polycrystals, but only described the size of the polycrystals as 100-400 nm, without mentioning the size of the cuprous oxide crystals constituting the polycrystals; CN101041456A synthesized cuprous oxide hollow submicrospheres formed by self-assembly of 11-22 nm cuprous oxide nanoparticles; CN107473258A synthesized cuprous oxide polycrystals composed of 10-20 nm cuprous oxide nanocrystals; CN101778799A synthesized spherical assembled particles formed by 1-100 nm ultrafine cuprous oxide particles; CN109485084A synthesized cuprous oxide cubes or microspheres assembled from cuprous oxide nanoparticles; Reference 13 (Small, 2022, 18(15),2107422.) synthesized cuprous oxide hollow assembled spherical shells, but none of the above includes any description of the size control of the small-sized units that constitute the cuprous oxide particles. Patent CN105905936A introduces two cuprous oxide nanocrystal assemblies with different morphologies, CNA-1 and CNA-2, and the sizes of the nanocrystals that constitute the particles are 32 nm and 10 nm, respectively, but does not include a multi-level controllable regulation method for a large span of crystal sizes from nanometers to micrometers. In addition, document 12 synthesized cuprous oxide hollow sub-microspheres with a particle size of 200 nm, but during the reaction process, only the size of the microsphere particles increased, and the size of the surface particles changed from 10 nm to 11 nm, which was almost unchanged.
[0007] Therefore, it is of great significance to study a method for preparing micro-nanostructured cuprous oxide polycrystalline particles to solve the problems existing in the prior art. Summary of the invention
[0008] The purpose of the present invention is to solve the problems existing in the prior art and provide a method for preparing micro-nanostructured cuprous oxide polycrystalline particles.
[0009] To achieve the above object, the technical solution adopted by the present invention is as follows:
[0010] A method for preparing micro-nanostructured cuprous oxide polycrystalline particles comprises the following steps: firstly dropping an organic amine aqueous solution into an aqueous solution of a divalent copper salt, stirring the solution for reaction, then dropping a reducing agent solution into the reaction solution, continuing the stirring for reaction, centrifuging and drying the reaction solution to obtain the micro-nanostructured cuprous oxide polycrystalline particles;
[0011] The micro-nanostructured cuprous oxide polycrystalline particles are nearly spherical in shape macroscopically, and the average particle size of the micro-nanostructured cuprous oxide polycrystalline particles is 1-2.3 μm. The micro-nanostructured cuprous oxide polycrystalline particles are formed by the co-growth of small-sized cuprous oxide crystals, and the small-sized cuprous oxide crystals are nearly spherical truncated octahedral in shape.
[0012] The grain size of the small-sized cuprous oxide crystals constituting the micro-nanostructured cuprous oxide polycrystalline particles is determined by the type of organic amine. The selected organic amine is characterized in that the molecular weight is less than 200 and the main chain contains only one amino group. The organic amine is one or more of aniline, furfurylamine, benzylamine, phenylethylamine and n-butylamine. The grain size of the small-sized cuprous oxide crystals (calculated by XRD spectrum) is 40~600 nm.
[0013] As the preferred technical solution:
[0014] The method for preparing the micro-nanostructured cuprous oxide polycrystalline particles as described above comprises the following specific steps:
[0015] (1) Slowly adding an organic amine aqueous solution to a uniform and stable divalent copper salt aqueous solution under mechanical stirring at a rate of 200 to 500 rpm at a rate of 1 to 10 mL / min. After the addition is completed, stirring and reacting for 0.5 to 5 h to obtain a mixed solution;
[0016] (2) Slowly adding the reducing agent aqueous solution to the mixed solution obtained in step (1) under mechanical stirring at a rate of 200 to 500 rpm, with a dropping rate of 1.25 to 7.5 mL / min. After the addition is completed, the stirring reaction is continued for 0.25 to 3 h until the color of the reaction solution tends to be stable, and the reaction solution is centrifuged to collect the reaction product;
[0017] (3) Wash the solid component obtained in step (3) with deionized water and ethanol, and vacuum dry it in a vacuum oven at 50 to 80° C. for 6 to 12 h to obtain micro-nanostructured cuprous oxide polycrystalline particles.
[0018] In the method for preparing micro-nanostructured cuprous oxide polycrystalline particles as described above, in step (1) and step (2), the reaction temperature is 20-80° C. and the reaction pressure is 0.1 MPa.
[0019] In the method for preparing micro-nanostructured cuprous oxide polycrystalline particles as described above, the divalent copper salt in step (1) is one or more of copper acetate, copper sulfate, copper nitrate and copper chloride, the concentration of the divalent copper salt aqueous solution is 0.1-1.2 M, and the concentration of the organic amine aqueous solution is 0.24-9.6 M.
[0020] In the method for preparing micro-nanostructured cuprous oxide polycrystalline particles as described above, the reducing agent in step (2) is one of hydrazine hydrate, ascorbic acid, glucose and sodium sulfite, and the concentration of the reducing agent aqueous solution is 0.07-2.0 M.
[0021] In the method for preparing micro-nanostructured cuprous oxide polycrystalline particles as described above, the molar ratio of the divalent copper salt, the organic amine and the reducing agent is 1:0.6~2:0.525~2.
[0022] In the method for preparing micro-nanostructured cuprous oxide polycrystalline particles as described above, the purity of the micro-nanostructured cuprous oxide polycrystalline particles (i.e., the mass proportion of the micro-nanostructured cuprous oxide polycrystalline particles in the product) is greater than 95%.
[0023] According to the method for preparing micro-nanostructured cuprous oxide polycrystalline particles, the thermal weight loss of the micro-nanostructured cuprous oxide polycrystalline particles is less than 4%.
[0024] Principle of the invention:
[0025] The present invention uses small molecule amine as a raw material, which actually replaces the role of the base and the dispersant / template agent in the prior art in one step. By adjusting the steric hindrance of the small molecule amine, the size of the nanocrystals constituting the cuprous oxide polycrystalline particles can be accurately controlled on a larger scale. Moreover, due to the small molecular weight of the amine, it is easier to remove from the product by washing or heating than a large molecular weight template agent, without affecting the purity and thermal stability of the product.
[0026] The present invention forms a coordination bond with divalent copper ions through the amino group of the organic amine, and forms a planar ion structure similar to tetraammine copper in the solution. If the small molecule amine contains an aromatic ring, the large steric hindrance of the aromatic ring group connected to the amino group forms dense protection for the copper ions in four directions, limits the attack of the reducing agent on the copper ions, thereby slowing down the growth rate of the cuprous oxide crystals, forming small-sized crystal grains, and thus achieving the purpose of controlling the crystal grain size. There are many types of small molecule unit primary amines with similar chemical composition and structure. When there is a large-sized aromatic ring in the molecule, the shorter the carbon chain connected between the aromatic ring and the amino group is, the closer the aromatic ring is to the copper ion, the stronger the protective effect on the copper ion, the smaller the chance of the copper ion being attacked by the reducing agent, the smaller the size of the crystal grain, and the opposite is true when the carbon chain between the aromatic ring and the amino group is longer. When the small molecule amine does not have an aromatic ring and only has one alkane chain, the steric hindrance is minimum, the protection of the central copper ion is the weakest, and it is correspondingly most likely to be attacked by the reducing agent to make the crystal grain grow into a larger size. In summary, by selecting small molecule amines with specific steric hindrance during synthesis, the crystal size of the particles can be precisely controlled, thereby achieving multi-level controllable regulation of the size of micro-nanostructured cuprous oxide polycrystalline particles.
[0027] The present invention provides a method for preparing micro-nanostructured cuprous oxide polycrystalline particles. When other conditions remain the same, the particle size of the micro-nanostructured cuprous oxide polycrystalline particles can be regulated within the range of 40 to 600 nm by selecting different small molecule amines. Specifically, the order of selecting aniline, furfurylamine, benzylamine, phenylethylamine, and n-butylamine as raw materials gradually increases the size of the crystals in the obtained particles. The principle is as follows:
[0028] After the small amine molecules enter the aqueous solution of divalent copper salt, a part of them will coordinate with the divalent copper ions. Specifically, four amine molecules act as ligands with one copper ion to form a complex ion similar to the structure of tetraammine copper. The reaction equation is as follows:
[0029] Cu 2+ + 4 R-NH2 → [Cu(H2N-R)4] 2+ ;
[0030] In the formula, R refers to the group connected to the amino group in the five small molecule amines;
[0031] Small molecular amines such as aniline, furfurylamine, benzylamine, phenylethylamine, and n-butylamine produce different steric hindrances after coordination with copper ions.
[0032] Among the small molecule amines containing aromatic rings, aniline has the shortest carbon chain length. The benzene ring is directly connected to the amino group, resulting in a close distance between the copper at the center of the ligand ion and the four surrounding benzene rings, forming a structure in which the four benzene rings tightly wrap the copper ion. The steric hindrance formed is the largest among the five small molecule amines. The carbon chain lengths of furfural amine and benzylamine are second, and there is a carbon between the aromatic ring and the amino group, so that there is a certain distance between the four larger aromatic rings and copper. The aromatic ring does not wrap the copper as tightly as aniline, and has a certain exposed space. Since the furan ring size of furfural amine is slightly smaller than that of benzylamine, The benzene ring makes the steric hindrance of furfurylamine to copper ions slightly smaller than that of benzylamine. Among the small molecule amines containing aromatic rings, phenylethylamine has the longest carbon chain. There are two carbon atoms between the aromatic ring and the amino group, which makes the larger aromatic ring as far away from the copper ions as possible, and has less protective effect on the copper ions. Compared with the small molecule amines containing aromatic rings, n-butylamine, which has only one carbon chain, has only one stretched carbon chain. After the amino group is connected to the copper ion, the steric hindrance formed is much smaller than that of the other four amines with large directional rings. The copper ion is fully exposed and is most likely to come into contact with the outside world. Therefore, after the five small molecule amines are coordinated with copper ions, the order of the steric hindrance strength to copper ions is: aniline>furfurylamine>benzylamine>phenylethylamine>n-butylamine, corresponding to the coating strength of small molecule amines to copper ions, such as Figure 1 As shown, it can be seen that the degree of copper coating by amines in the ligand ions decreases successively.
[0033] Furthermore, during the reduction reaction, due to the different coating strengths of the ligands formed by the four amines on the copper ions, after the crystal nucleation, the ligands with stronger coating are the most difficult to attack by the reducing agent due to their good protection of divalent copper, making it difficult for the size of the crystal to grow after nucleation, and tend to re-nucleate and grow into a small grain size, while the ligands with weaker coating can attack the divalent copper at the center of the ligand ion more smoothly, so that the reduction reaction can proceed more smoothly. After the crystal nucleation, the grain size increases rapidly with the reduction reaction, and eventually grows into large grains. This can precisely control the grain size by regulating the steric hindrance. Crystals of different sizes will eventually agglomerate under the driving force generated by the trend of surface energy reduction, and further grow together to form micro-nanostructured cuprous oxide polycrystalline particles.
[0034] Beneficial effects:
[0035] (1) A method for preparing micro-nanostructured cuprous oxide polycrystalline particles of the present invention replaces the high molecular weight dispersant and inorganic bases in the existing process with small molecule amines in one step. The small molecule amines have simple molecular structures, and have the advantages of low price, good water solubility and low toxicity. At the same time, due to their low molecular weight, they are easily removed from the product as much as possible by means of water washing and heating, thereby ensuring that the final cuprous oxide powder product has a high purity. In addition, by controlling the type of small molecule amines, the size of small-sized crystals constituting the polycrystalline particles can be regulated within the range of 40 to 600 nm. Specifically, the size of small-sized crystals constituting the micro-nanostructured cuprous oxide polycrystalline particles gradually increases in the order of aniline, furfurylamine, benzylamine, phenethylamine and n-butylamine. Thus, cuprous oxide polycrystalline particles with a gradient change in morphology are obtained.
[0036] (2) The present invention provides a method for preparing micro-nanostructured cuprous oxide polycrystalline particles. The crystal particle size constituting the polycrystalline particles can be controllably adjusted within the range of 40 to 600 nm by selecting different organic amines. The method has the advantages of mild reaction conditions, simple raw material types, low synthesis cost, and controllable product morphology.
[0037] (3) The method for preparing micro-nanostructured cuprous oxide polycrystalline particles of the present invention is gentle and safe, with the reaction being carried out at normal pressure and near room temperature. There are only three types of reaction raw materials, and the one-pot synthesis process is simple and controllable. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 It is the coordination reaction formula of five small molecular amines, aniline, furfurylamine, benzylamine, phenylethylamine and n-butylamine, with copper ions;
[0039] Figure 2 The SEM images of the micro-nanostructured cuprous oxide particles obtained in Example 1 at different scales; the scale of the left image is 1 μm, and the scale of the right image is 10 μm;
[0040] Figure 3 The SEM images of the micro-nanostructured cuprous oxide particles obtained in Example 2 at different scales; the scale of the left image is 1 μm, and the scale of the right image is 10 μm;
[0041] Figure 4 The SEM images of the micro-nanostructured cuprous oxide particles obtained in Example 3 at different scales; the scale of the left image is 1 μm, and the scale of the right image is 10 μm;
[0042] Figure 5 The SEM images of the micro-nanostructured cuprous oxide particles obtained in Example 4 at different scales; the scale of the left image is 1 μm, and the scale of the right image is 10 μm;
[0043] Figure 6 The SEM images of the micro-nanostructured cuprous oxide particles obtained in Example 5 at different scales; the scale of the left image is 1 μm, and the scale of the right image is 10 μm;
[0044] Figure 7 The SEM images of the micro-nanostructured cuprous oxide particles obtained in Comparative Example 1 at different scales; the scale of the left image is 1 μm, and the scale of the right image is 10 μm;
[0045] Figure 8 The thermogravimetric curves of Example 1, Example 2 and Example 3 are shown;
[0046] Fig. 9 It is a bar graph of the antiviral rates of commercially available 100 nm cuprous oxide, commercially available 1000 nm cuprous oxide, Example 1, and Example 3;
[0047] Fig.10 XRD diagram of the micro-nanostructured cuprous oxide particles obtained in Examples 1 to 5;
[0048] Fig.11 3 are structural explanation diagrams of Example 3, wherein the left figure is a SEM image of the micro-nanostructured cuprous oxide particles obtained at a scale of 1 μm, and the right figure is a typical truncated octahedral grain of cuprous oxide. DETAILED DESCRIPTION
[0049] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0050] The test methods involved in the performance indicators of the present invention are as follows:
[0051] Scanning electron microscope images: taken using a Regulus8230 field emission scanning electron microscope (HITACHI, Japan).
[0052] Thermal gravimetric curve: The test was carried out using a TG209F1 thermogravimetric analyzer (NETZSCH, Germany) under a nitrogen atmosphere, with a purge gas rate of 40 mL / min, a protective gas rate of 20 mL / min, a heating rate of 10°C / min, and an actual test range of 30~700°C.
[0053] XRD spectrum: The test was carried out using a D8 Advance in-situ electrochemical X-ray diffractometer (Bruker, USA), where a copper target was used, the test step size was 0.01°, and the test 2θ range was 10°~90°.
[0054] Antiviral rate (virus inhibition rate): tested in accordance with ISO 18184-2019 standard, and the test virus is HCoV-OC43 virus.
[0055] Commercially available 100 nm cuprous oxide was purchased from Beijing Zhongke Keyou Technology Co., Ltd. Nano cuprous oxide powder (spherical, 100 nm).
[0056] Commercially available 1000 nm cuprous oxide was purchased from Anhui Kerun Nanotechnology Co., Ltd.
[0057] Example 1
[0058] A method for preparing micro-nanostructured cuprous oxide polycrystalline particles, the specific steps are as follows:
[0059] (1) Under the conditions of mechanical stirring at a rate of 500 rpm, a reaction temperature of 60°C and a reaction pressure of 0.1 MPa, a 1.8 M aniline aqueous solution was slowly added dropwise to a uniform and stable 0.3 M copper nitrate aqueous solution at a dropping rate of 5 mL / min. After the addition was completed, the stirring reaction was continued for 3 h to obtain a mixed solution;
[0060] (2) Under the conditions of mechanical stirring at a rate of 500 rpm, a reaction temperature of 60° C. and a reaction pressure of 0.1 MPa, slowly dropwise add a 0.8 M glucose aqueous solution into the mixed solution obtained in step (1) at a dropwise acceleration rate of 2.0 mL / min. After the dropwise addition is completed, continue stirring the reaction for 2 h, and centrifuge the reaction solution to collect the reaction product;
[0061] The molar ratio of copper nitrate, aniline and glucose is 1:1.5:2;
[0062] (3) The solid component obtained in step (3) is washed with deionized water and ethanol, and vacuum dried in a vacuum oven at 60° C. for 10 h to obtain micro-nanostructured cuprous oxide polycrystalline particles.
[0063] like Figure 2 As shown in the figure, the average particle size of the finally prepared micro-nanostructured cuprous oxide polycrystalline particles is 1.0 μm, and the micro-nanostructured cuprous oxide polycrystalline particles are formed by the co-growth of small-sized cuprous oxide crystals with a grain size of 40 nm; the purity of the micro-nanostructured cuprous oxide polycrystalline particles is 95.6%; as shown in the figure Figure 8 As shown in the figure, the thermal weight loss of the micro-nanostructured cuprous oxide polycrystalline particles is 3.59%; referring to the ISO 18184-2019 standard test, the antiviral rate against HCoV-OC43 virus within 3 minutes is 99.07%, which has a good antiviral effect.
[0064] Example 2
[0065] A method for preparing micro-nanostructured cuprous oxide polycrystalline particles, the specific steps are as follows:
[0066] (1) Under the conditions of mechanical stirring at a rate of 400 rpm, a reaction temperature of 20°C and a reaction pressure of 0.1 MPa, a 6.0 M furfurylamine aqueous solution was slowly added dropwise to a uniform and stable 1.0 M copper sulfate aqueous solution at a dropping rate of 2 mL / min. After the addition was completed, the stirring reaction was continued for 1 h to obtain a mixed solution;
[0067] (2) Under the conditions of mechanical stirring at a rate of 400 rpm, a reaction temperature of 20° C. and a reaction pressure of 0.1 MPa, slowly dropwise add a 1.0 M ascorbic acid aqueous solution to the mixed solution obtained in step (1) at a dropwise rate of 2.5 mL / min. After the dropwise addition is completed, continue stirring the reaction for 0.5 h, and centrifuge the reaction solution to collect the reaction product;
[0068] Wherein, the molar ratio of copper sulfate, furfural amine and ascorbic acid is 1:1.5:0.75;
[0069] (3) The solid component obtained in step (3) is washed with deionized water and ethanol, and vacuum dried in a vacuum oven at 80° C. for 6 h to obtain micro-nanostructured cuprous oxide polycrystalline particles.
[0070] like Figure 3 As shown in the figure, the average particle size of the finally prepared micro-nanostructured cuprous oxide polycrystalline particles is 1.5 μm, and the micro-nanostructured cuprous oxide polycrystalline particles are formed by the co-growth of small-sized cuprous oxide crystals with a grain size of 150 nm; the purity of the micro-nanostructured cuprous oxide polycrystalline particles is 97.2%; Figure 8 As shown, the thermal weight loss of the micro-nanostructured cuprous oxide polycrystalline particles is 1.25%.
[0071] Comparative Example 1
[0072] A method for preparing micro-nanostructured cuprous oxide polycrystalline particles is basically the same as that of Example 2, except that the furfurylamine aqueous solution in step (1) is replaced by a NaOH solution of equimolar concentration.
[0073] like Figure 7 As shown, the cuprous oxide prepared in Comparative Example 1 does not have an independent particle structure, but appears as a large-volume growing cuprous oxide agglomerate, some of which have a size of more than ten microns and have an obvious large-grain growth structure. Since the particle structure cannot be observed and the intercalation and agglomeration between crystals result in a large overall size, it is impossible to calculate the particle size, which proves that the small-molecule amine does not only provide an alkaline environment in the formation process of the micro-nanostructured cuprous oxide polycrystalline particles, but its specific group connected to the amino group also plays a specific effect to promote the formation of the independent particle structure of cuprous oxide.
[0074] Example 3
[0075] A method for preparing micro-nanostructured cuprous oxide polycrystalline particles, the specific steps are as follows:
[0076] (1) Under the conditions of mechanical stirring at a rate of 300 rpm, a reaction temperature of 20°C and a reaction pressure of 0.1 MPa, a 0.24 M benzylamine aqueous solution was slowly added dropwise to a uniform and stable 0.1 M copper acetate aqueous solution at a rate of 10 mL / min. After the addition was completed, the reaction was continued with stirring for 5 h to obtain a mixed solution;
[0077] (2) Under the conditions of mechanical stirring at a rate of 300 rpm, a reaction temperature of 20° C. and a reaction pressure of 0.1 MPa, slowly dropwise add a 0.07 M hydrazine hydrate aqueous solution to the mixed solution obtained in step (1) at a dropwise acceleration rate of 7.5 mL / min. After the dropwise addition is completed, continue stirring the reaction for 0.25 h, and centrifuge the reaction solution to collect the reaction product;
[0078] Wherein, the molar ratio of copper acetate, benzylamine and hydrazine hydrate is 1:0.6:0.525;
[0079] (3) The solid component obtained in step (3) is washed with deionized water and ethanol, and vacuum dried in a vacuum oven at 50° C. for 12 h to obtain micro-nanostructured cuprous oxide polycrystalline particles.
[0080] like Figure 4 As shown in the figure, the average particle size of the finally prepared micro-nanostructured cuprous oxide polycrystalline particles is 1.7 μm, and the micro-nanostructured cuprous oxide polycrystalline particles are formed by the co-growth of small-sized cuprous oxide crystals with a grain size of 240 nm; the purity of the micro-nanostructured cuprous oxide polycrystalline particles is 98.1%; as shown in the figure Figure 8 As shown, the thermal weight loss of the micro-nanostructured cuprous oxide polycrystalline particles is 1.34%; referring to the ISO 18184-2019 standard test, the antiviral rate against HCoV-OC43 virus within 3 minutes is 84.50%.
[0081] like Fig. 9 As shown, compared with the antiviral rates of commercially available 100 nm cuprous oxide (Cu2O-100) and commercially available 1000 nm cuprous oxide (Cu2O-1000), which can only reach 72.67% and 71.67%, the micro-nanostructured cuprous oxide polycrystalline particles synthesized in the present invention have significantly better antiviral effects, especially the antiviral rate of Example 1 can reach 99.07%, showing better performance than nano-scale particles, while Example 3 is second, at 84.50%. This may be because the micro-nanostructure of the material gives the particles a larger specific surface area, which increases the chances of polycrystalline particles coming into contact with viruses under low agglomeration conditions. In addition to the specific surface area, according to reference 14 (Nano Lett., 2020, 20: 5367-5375.), the rough structure formed by the crystals accumulated on the surface of the micro-nano structure makes it easy for the virus to be enriched or tightly embedded with the material, and the smaller the grain size on the surface is, the closer it is to the size of the virus itself or the surface structure of the virus, and the more obvious this effect may be. This also explains why the antiviral effect of Example 1 is stronger than that of Example 3. According to literature 15 (Appl. Surf. Sci., 2019, 465: 279-287.), the (111) crystal plane of cuprous oxide crystals generally has higher activity in applications, and among various forms of cuprous oxide, the octahedral form has the highest (111) crystal plane exposure ratio. The cuprous oxide crystals constituting the micro-nanostructured cuprous oxide polycrystalline particles of the present invention have a truncated octahedral form and also have a higher (111) crystal plane exposure ratio. Therefore, compared with common spherical or amorphous crystals, they have higher antiviral activity and can achieve better antiviral effects than conventional nano-scale cuprous oxide.
[0082] like Fig.11 As shown, the eight hexagonal faces of the truncated octahedron correspond to the (111) crystal plane of cuprous oxide, and the six quadrilateral faces correspond to the (100) crystal plane of cuprous oxide. The grain interpretation is based on reference 16 (Prog. Mater Sci., 2018, 96:111-173.); by comparing with the standard grain morphology of cuprous oxide in the literature, it is shown that the small-sized cuprous oxide crystals are in the form of truncated octahedrons, and the crystal plane structure of the cuprous oxide grains is further determined.
[0083] Example 4
[0084] A method for preparing micro-nanostructured cuprous oxide polycrystalline particles, the specific steps are as follows:
[0085] (1) Under the conditions of mechanical stirring at a rate of 200 rpm, a reaction temperature of 80°C and a reaction pressure of 0.1 MPa, a 9.6 M phenylethylamine aqueous solution was slowly added dropwise to a uniform and stable 1.2 M copper chloride aqueous solution at a dropping rate of 1 mL / min. After the addition was completed, the stirring reaction was continued for 0.5 h to obtain a mixed solution;
[0086] (2) Under the conditions of mechanical stirring at a rate of 200 rpm, a reaction temperature of 80° C. and a reaction pressure of 0.1 MPa, slowly dropwise add a 2.0 M sodium sulfite aqueous solution to the mixed solution obtained in step (1) at a dropwise acceleration rate of 1.25 mL / min. After the dropwise addition is completed, continue stirring the reaction for 3 h, and centrifuge the reaction solution to collect the reaction product;
[0087] Wherein, the molar ratio of copper chloride, phenylethylamine and sodium sulfite is 1:2:1.25;
[0088] (3) The solid component obtained in step (3) is washed with deionized water and ethanol, and vacuum dried in a vacuum oven at 80° C. for 6 h to obtain micro-nanostructured cuprous oxide polycrystalline particles.
[0089] like Figure 5 As shown, the average particle size of the finally prepared micro-nanostructured cuprous oxide polycrystalline particles is 2.3 μm, and the micro-nanostructured cuprous oxide polycrystalline particles are formed by the co-growth of small-sized cuprous oxide crystals with a grain size of 400 nm; the purity of the micro-nanostructured cuprous oxide polycrystalline particles is 97.6%; and the thermal weight loss of the micro-nanostructured cuprous oxide polycrystalline particles is 1.28%.
[0090] Example 5
[0091] A method for preparing micro-nanostructured cuprous oxide polycrystalline particles, the specific steps are as follows:
[0092] (1) Under the conditions of mechanical stirring at a rate of 300 rpm, a reaction temperature of 20°C and a reaction pressure of 0.1 MPa, a 0.24 M n-butylamine aqueous solution was slowly added dropwise to a uniform and stable 0.1 M copper acetate aqueous solution at a dropping rate of 5 mL / min. After the addition was completed, the stirring reaction was continued for 5 h to obtain a mixed solution;
[0093] (2) Under the conditions of mechanical stirring at a rate of 300 rpm, a reaction temperature of 20° C. and a reaction pressure of 0.1 MPa, slowly dropwise add a 0.07 M hydrazine hydrate aqueous solution to the mixed solution obtained in step (1) at a dropwise acceleration rate of 7.5 mL / min. After the dropwise addition is completed, continue stirring the reaction for 0.25 h, and centrifuge the reaction solution to collect the reaction product;
[0094] Wherein, the molar ratio of cupric acetate, n-butylamine and hydrazine hydrate is 1:0.6:0.525;
[0095] (3) The solid component obtained in step (3) is washed with deionized water and ethanol, and vacuum dried in a vacuum oven at 50° C. for 12 h to obtain micro-nanostructured cuprous oxide polycrystalline particles.
[0096] like Figure 6 As shown, the average particle size of the finally prepared micro-nanostructured cuprous oxide polycrystalline particles is 1.0 μm, and the micro-nanostructured cuprous oxide polycrystalline particles are formed by the co-growth of small-sized cuprous oxide crystals with a grain size of 600 nm; the purity of the micro-nanostructured cuprous oxide polycrystalline particles is 98.4%; and the thermal weight loss of the micro-nanostructured cuprous oxide polycrystalline particles is 1.02%.
[0097] according to Fig.10 The XRD spectra shown in the figure show that the peaks gradually become sharper from Example 1 to Example 5, and the half-peak width of the diffraction peak gradually decreases, indicating that the grain size of the micro-nanostructured cuprous oxide polycrystalline particles gradually increases. The half-peak width of the strongest diffraction peak of cuprous oxide at 36.418° is substituted into the Scherrer formula to calculate the actual grain size value, which is consistent with the trend shown in the SEM image, proving that the present invention can indeed accurately control the grain size in the cuprous oxide particles.
Claims
1. A method for preparing micro-nanostructured cuprous oxide polycrystalline particles, characterized in that: First, an organic amine aqueous solution is added dropwise to an aqueous solution of a divalent copper salt, and after stirring for reaction, a reducing agent solution is added dropwise to the reaction solution, and after continuing to stir for reaction, the reaction solution is centrifuged and dried to obtain micro-nanostructured cuprous oxide polycrystalline particles; The average particle size of the micro-nanostructured cuprous oxide polycrystalline particles is 1-2.3 μm, and the micro-nanostructured cuprous oxide polycrystalline particles are formed by the co-growth of small-sized cuprous oxide crystals. The grain size of the small-sized cuprous oxide crystals constituting the micro-nanostructured cuprous oxide polycrystalline particles is determined by the type of organic amine, which is one or more of aniline, furfurylamine, benzylamine, phenylethylamine and n-butylamine. The grain size of the small-sized cuprous oxide crystals is 40-600 nm.
2. The method for preparing micro-nanostructured cuprous oxide polycrystalline particles according to claim 1, characterized in that: The specific steps are as follows: (1) Slowly adding an organic amine aqueous solution to a uniform and stable divalent copper salt aqueous solution under mechanical stirring at a rate of 200 to 500 rpm at a rate of 1 to 10 mL / min. After the addition is completed, stirring and reacting for 0.5 to 5 h to obtain a mixed solution; (2) slowly adding the reducing agent aqueous solution to the mixed solution obtained in step (1) under mechanical stirring at a rate of 200 to 500 rpm, with a dropping rate of 1.25 to 7.5 mL / min. After the addition is completed, the stirring reaction is continued for 0.25 to 3 h, and the reaction solution is centrifuged to collect the reaction product; (3) Wash the solid component obtained in step (3) with deionized water and ethanol, and vacuum dry it in a vacuum oven at 50 to 80° C. for 6 to 12 h to obtain micro-nanostructured cuprous oxide polycrystalline particles.
3. The method for preparing micro-nanostructured cuprous oxide polycrystalline particles according to claim 2, characterized in that: In step (1) and step (2), the reaction temperature is 20-80°C and the reaction pressure is 0.1 MPa.
4. The method for preparing micro-nanostructured cuprous oxide polycrystalline particles according to claim 2, characterized in that: In step (1), the divalent copper salt is one or more of copper acetate, copper sulfate, copper nitrate and copper chloride, the concentration of the divalent copper salt aqueous solution is 0.1-1.2 M, and the concentration of the organic amine aqueous solution is 0.24-9.6 M.
5. The method for preparing micro-nanostructured cuprous oxide polycrystalline particles according to claim 2, characterized in that: In step (2), the reducing agent is one of hydrazine hydrate, ascorbic acid, glucose or sodium sulfite, and the concentration of the reducing agent aqueous solution is 0.07~2.0 M.
6. The method for preparing micro-nanostructured cuprous oxide polycrystalline particles according to claim 2, characterized in that: The molar ratio of the divalent copper salt, the organic amine and the reducing agent is 1:0.6~2:0.525~2.
7. The method for preparing micro-nanostructured cuprous oxide polycrystalline particles according to claim 2, characterized in that: The purity of the micro-nanostructured cuprous oxide polycrystalline particles is greater than 95%.
8. The method for preparing micro-nanostructured cuprous oxide polycrystalline particles according to claim 7, characterized in that: The thermal weight loss of micro-nanostructured cuprous oxide polycrystalline particles is less than 4%.
Citation Information
Patent Citations
Method for preparing monodispersed copper-protoxide hollow microsphere by aqueous phase cluster soft mold plates process
CN101041456A
Spherical assembly particle composition of cuprous oxide and preparation method thereof
CN101778799A
Method for preparing ordered nano cuprous oxide polycrystalline powder
CN101905899A
Preparation method of micro-nano cuprous oxide particles with controllable morphology and size
CN104261457A
A kind of double-layer structure cuprous oxide nano-microsphere and preparation method thereof
CN104445358B